2020
DOI: 10.3390/ijms21113899
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile and Desaturase Activities in 7–10-Year-Old Children Attending Primary School in Verona South District: Association between Palmitoleic Acid, SCD-16, Indices of Adiposity, and Blood Pressure

Abstract: In previous studies, dietary and circulating fatty acids (FA) and desaturases activity (delta-5 desaturase [D5D], delta-6 desaturase [D6D], and stearoyl-CoA desaturase [SCD-16]) involved in their metabolism were associated with metabolic and cardiovascular disorders. The aim of the study was to assess the association between different FAs and desaturases activity (estimated as product:precursor ratios) with individual cardiovascular risk factors (in particular, anthropometric measurements and blood pressure [B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
5
7
2
Order By: Relevance
“…The same holds true upon subdivision of our group of subjects into children <9 and >9 years old, in order to facilitate a direct comparison with literature data relative to children of different age ranges. The levels of ω3 PUFA ALA and EPA were substantially in line with those present in the literature, whereas DHA levels were also lower [37][38][39][40][41]. It is important to note that the FA values observed in normal children by our group and reported in [37] referred to normal weight or overweight children, in line with the characteristics of the subjects observed in this study, whereas Bonafini et al reported the data of normal weight children only [39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The same holds true upon subdivision of our group of subjects into children <9 and >9 years old, in order to facilitate a direct comparison with literature data relative to children of different age ranges. The levels of ω3 PUFA ALA and EPA were substantially in line with those present in the literature, whereas DHA levels were also lower [37][38][39][40][41]. It is important to note that the FA values observed in normal children by our group and reported in [37] referred to normal weight or overweight children, in line with the characteristics of the subjects observed in this study, whereas Bonafini et al reported the data of normal weight children only [39].…”
Section: Discussionsupporting
confidence: 92%
“…The omega 3 index (OI3), calculated as described by Stark [36], ranged from 1.60% to 4.15% with a mean of 2.35%, with only one case where the O3I was higher than 4%, while all others cases were below the value of 3%. We compared the relative quantities of some representative FA assessed in this study with the relative quantities reported by other studies (Table 4) in which the FA profile was obtained analyzing the whole blood of children and/or adolescents [37][38][39][40][41]. For studies examining differences in FA profile between control and pathological subjects, the values of the control group were considered.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ratio of n-3: n-6 fatty acids might affect the PUFAs metabolism. As reported, the activity of SCD, D5D, D6D was associated with metabolic-related diseases [54]. In this study, similarly, SCD-18 and D5D had positive relationships with cognitive function scores, instead, SCD-16 and D6D showed opposite results.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, ratio of n-3: n-6 fatty acids might affect the PUFAs metabolism. As reported, the activity of SCD, D5D, D6D was associated with metabolic-related diseases (Bona ni et al, 2020). In this study, similarly, SCD-18 and D5D had positive relationships with cognitive function scores, instead, SCD-16 and D6D showed opposite results.…”
Section: Discussionsupporting
confidence: 63%